Current advances in skin-on-a-chip models for drug testing - Zhang, Qiang; Sito, Linda; Mao, Mao; He, Jiankang; Zhang, Yu Shrike; Zhao, Xin (Microphysiological Systems, 2018)
Skin-on-a-chip models are highly desirable in drug testing compared to conventional 2D cell culture and animal models as they can replicate organ-specific 3D structural organization and physiological functions at a relatively low cost. To engineer a physiologically relevant skin model, human skin structures have been integrated onto microfluidic platforms to construct skin-on-a-chip systems that can mimic the complex in vivo situation. In this mini-review, we first briefly introduce some critical technologies employed to develop in vitro skin-on-a-chip models. We then review the applications of the state-of-the-art skin-on-a-chip models in drug testing, with a focus on using models of full-thickness skin equivalents (FTSEs), skin models with additional components such as vasculature, immune cells and hair follicles as well as multi-organ-on-a-chip models. Finally, we discuss some current challenges and future directions of development of complex, and in vivo-like skin-on-a-chip models.